2019
DOI: 10.1182/blood-2018-11-876839
|View full text |Cite
|
Sign up to set email alerts
|

Bad weed: synthetic cannabinoid–associated coagulopathy

Abstract: Recent multistate outbreaks of coagulopathy caused by brodifacoum-tainted synthetic cannabinoids or “fake weed” highlight the public health impact of long-acting anticoagulant rodenticides (LAARs). Patients presenting with this syndrome have had recent exposure to synthetic cannabinoids, evidence of isolated vitamin K antagonism with or without bleeding, and detectable levels of brodifacoum and other LAARs in circulation. This article will provide information on synthetic cannabinoids, LAARs, and coagulopathic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Recently, a painless macro-hematuria with altered coagulation was described in association with SC use, though no anticoagulant poisoning panel was performed [47]. Additionally, there were reports about products containing SCs allegedly laced with potent anticoagulant coumarin derivatives like brodifacoum and difenacoum [48,49]. In our case, to verify if the kidney bleedings could have been caused by such contaminants, the analysis of coumarin derivatives including super-warfarintype drugs was performed, but was found negative.…”
Section: Discussionmentioning
confidence: 77%
“…Recently, a painless macro-hematuria with altered coagulation was described in association with SC use, though no anticoagulant poisoning panel was performed [47]. Additionally, there were reports about products containing SCs allegedly laced with potent anticoagulant coumarin derivatives like brodifacoum and difenacoum [48,49]. In our case, to verify if the kidney bleedings could have been caused by such contaminants, the analysis of coumarin derivatives including super-warfarintype drugs was performed, but was found negative.…”
Section: Discussionmentioning
confidence: 77%
“…3,9,71 A major outbreak of synthetic cannabinoidassociated coagulopathy occurred in Illinois, US in 2018, with a total of over 300 persons being affected and a total of 7 deaths between March and October 2018. 9,13,16 In the case series by Kelkar et al, brodifacoum was identified as the culprit and was detected in all patients tested, whereas difenacoum, bromadiolone, and warfarin were additionally detected among the patients. 16 Limited experimental data suggests that there is no pharmacodynamics interaction between brodifacoum and synthetic cannabinoids, though pharmacokinetic interactions have not been ruled out.…”
Section: Epidemiology Of Superwarfarin Poisoningmentioning
confidence: 94%
“…[7][8][9][10] The significant morbidity and mortality from superwarfarin can be contrasted with the highly treatable nature of superwarfarin poisoning with factor replacement and vitamin K therapy, available in most parts of the world. 2,4,6,[11][12][13] The diagnosis of superwarfarin poisoning in patients without a clear history of exposure is difficult. Examples include victims of homicide attempts, 14,15 the unfortunate users of brodifacoum-laced synthetic cannabinoids in the recent Illinois outbreak, 9,16 and a substantial number of patients exposed to superwarfarins of yet uncertain origin in China and Hong Kong.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the aforementioned adverse effects associated with SCRA use are not typically observed following cannabis consumption . Cases of coagulopathies following SCRA consumption in the United States have recently been linked to the presence of a potent vitamin K antagonist (brodifacoum [ 9 ]) in certain batches of SCRA‐containing products . At present, it remains unclear if this presence of 9 in certain batches of SCRA‐containing products is deliberate or accidental.…”
Section: Introductionmentioning
confidence: 99%